(Non)alienation in Lithuanian Schools: the Case of Four High-School Seniors - Labokas, Juozapas (Acta Paedagogica Vilnensia, 2024)
This article focuses on the alienation manifested in the field of the teacher-student relationship. The study uses Morinaj, Hadjar and Hascher’s (2020) quantitative-diagnostic instrument for determining the level of alienation, with the help of which participants experiencing 2 high and 2 low alienation in relation to teachers were selected from the studied population of twelfth graders (n=227). The latter were invited to a qualitative semi-structured interview. The aim of this study was to better understand the problem of alienation in the student–teacher relation, discuss and reflect on the possibilities of the diagnostic instrument and reveal the experiences of (non)alienation of four research participants. It was found that the participants interpreted the statements of the instrument differently, giving different answers, which could potentially distort the results of the diagnostic study. The revealed diversity of pedagogical experiences showed that alienation is an individual and multifaceted phenomenon, thus it is meaningful to supplement further alienation research with a qualitative methodological perspective.
Keywords: school alienation; teacher-student relation; causes of alienation